Fidgety movements in infants born very preterm: predictive value for cerebral palsy in a clinical multicentre setting. (19th January 2017) - Datta, Alexandre N; Furrer, Mark A; Bernhardt, Iris; Hüppi, Petra S; Borradori‐Tolsa, Cristina; Bucher, Hans Ulrich; Latal, Beatrice; Grunt, Sebastian; Natalucci, Giancarlo; ,
Abstract : Aim: This study assessed predictive values of fidgety movement assessment (FMA) in a large sample of infants born very preterm for developmental abnormalities, in particular for cerebral palsy (CP) at 2 years in an everyday clinical setting. Method: This is a multicentre study of infants born preterm with gestational age lower than 32.0 weeks. FMA was performed at 3 months corrected age; neurodevelopment (Bayley Scales of Infant Development, 2nd edition) and neurological abnormalities were assessed at 2 years. Predictive values of FMA for the development of CP were calculated and combined with abnormalities at cerebral ultrasound. Results: Five hundred and thirty‐five infants (gestational age 28.2wks [standard deviation 1.3wks]) were included. Eighty‐one percent showed normal fidgety movements and 19% atypical (82 absent, 21 abnormal) fidgety movements. Absent fidgety movements predicted CP at 2 years with an odds ratio (OR) of 8.9 (95% confidence interval [CI] 4.1–17.0), a combination of atypical fidgety movements and major brain lesion on cerebral ultrasound predicted it with an OR of 17.8 (95% CI 5.2–61.6). Mean mental developmental index of infants with absent fidgety movements was significantly lower ( p =0.012) than with normal fidgety movements. Interpretation: Detection of infants at risk for later CP through FMA was good, but less robust when performed in a routine clinical setting; prediction improved when combined with neonatal cerebral ultrasound. What this paper adds: Fidgety movement assessment (FMA) in infants born very preterm is practicable in a clinical setting. Clinical results of FMA are less robust than when performed in academic settings. A combination of FMA and cerebral ultrasound appears to improve prognostic information. FMA at 3 months can help to identify infants at risk for cognitive dysfunction. This article is commented on by Zuk on page568 of this issue.